2011
DOI: 10.1364/ol.36.000787
|View full text |Cite
|
Sign up to set email alerts
|

Measuring vortex charge with a triangular aperture

Abstract: A triangular aperture illuminated with a vortex beam creates a truncated lattice diffraction pattern that identifies the charge of the vortex. In this Letter, we demonstrate the measurement of vortex charge via this approach for vortex beams up to charge ±7. We also demonstrate the use of this technique for measuring femtosecond vortices and noninteger vortices, comparing these results with numerical modeling. It is shown that this technique is simple and reliable, but care must be taken when interpreting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(32 citation statements)
references
References 12 publications
1
31
0
Order By: Relevance
“…Other methods have also been introduced to measure the OAM of optical vortices based on the diffraction phenomena [12][13][14]. More recently, it has been shown that a triangular aperture illuminated with a vortex beam creates a truncated lattice diffraction pattern and that the resultant diffraction pattern can be used to measure the OAM of light beams [15][16][17]. Other methods for measuring the topological charge of an optical vortex have included the diffraction intensity pattern after an axicon [18] or an annular triangle aperture [19].…”
mentioning
confidence: 99%
“…Other methods have also been introduced to measure the OAM of optical vortices based on the diffraction phenomena [12][13][14]. More recently, it has been shown that a triangular aperture illuminated with a vortex beam creates a truncated lattice diffraction pattern and that the resultant diffraction pattern can be used to measure the OAM of light beams [15][16][17]. Other methods for measuring the topological charge of an optical vortex have included the diffraction intensity pattern after an axicon [18] or an annular triangle aperture [19].…”
mentioning
confidence: 99%
“…Since Hickmann et al [9], in 2010, unveiled the truncated optical lattice in triangular-aperture diffraction of OAM beams, it has been used as a more effective method for OAM detection. This method is free of complicated interferometer devices and has been successfully used in femtosecond vortices [10], non-integer charge vortices [11], vectorial vortices [12], and elliptical vortex beams [13], which largely promoted the related technologies and applications. Therefore, it is very significant to fulfill the technical breakthrough by more characteristic structured lights for extending more novel applications.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, quite a few ways have been presented to measure the topological charge value of vortex beams161718192021222324. Generally, the light beams carrying OAM can be detected directly by observing the interference patterns.…”
mentioning
confidence: 99%
“…For instance, the measurement of the topological charge value of an optical vortex beam was reported by analyzing the interference pattern between a vortex beam and its mirror image16. A triangular aperture was also used for the measurement of vortex beams, which could be up to l  = ± 71718. Through the diffraction intensity pattern after an annular aperture, the measurement of the topological charge value of an optical vortex beam was also up to | l|  = 919.…”
mentioning
confidence: 99%